Common Errors Found in the Unpublished Theses of English Literature Study Program Students of Universitas Bina Darma - Dinda Amalia Utami; Dewi Purnama Sari (RETORIKA: Jurnal Ilmu Bahasa, 2025)
Thesis is a research paper in the form of a written that discusses a problem and one of the requirements for acquiring a bachelor’s degree at university. The thesis must be written correctly and must follow the rules of scientific writing. One of the rules in writing a thesis is using good grammar. Grammar is very important in writing a thesis, but some students still make errors in using grammar. The most grammar errors found is common error. This study had analyzed the common errors in the unpublished theses of English literature study program students of Universitas Bina Darma. The researcher was interested in analyzing this object because grammar is very important in research writing. Qualitative method with descriptive approach and case study design was used in this study. The hypothesis of kinds of common errors in this study used the theory by Keshavarz (2012). 15 unpublished theses of English literature study program students of the 2019 class of Universitas Bina Darma became the data source used in this study. The errors data were identified based on grammatical rules that were seen by context of the sentence, such as use of time and part of speech used in the sentence. So that the writing became grammatically correct in writing. The results of this study found 38 data and 4 kinds of common errors in it, they were: 13 omissions (34,2%), 5 additions (13,1%), 17 substitutions (44,8%), and 3 permutations (7,9%). The most dominant common error found was the substitution error with the number of 17 substitutions and the percentage of 44,8%